Identification of key controlling factors of ozone pollution in Jinan, northern China over 2013–2020 - Liang, Di; Yan, Huaizhong; Tian, Yong; Liu, Yalin; Hao, Saimei; Bai, Haoqiang; Zhang, Guiqin; Deng, Wei (Frontiers in Ecology and Evolution, 2022)
Urban ozone (O3) pollution has become a prominent environmental threat to public health while the relationship between O3 formation and driving factors remains elusive, particularly for megacities in Shandong Peninsula of China. In this study, we use intensive ambient measurements of trace gases to comprehensively investigate the magnitude of O3 pollution in Jinan city from 2013 to 2020. Further, emission inventory and OMI NO2 columns are used for probing changes in precursor emissions. Ground-level measurements indicate degraded O3 air quality afterwards 2015 and depict city-wide elevated O3 levels (higher than 140 µg/m3 in the warm season). For precursor emissions, it is found that NOx emissions have decreased more than 30% due to successful regulation efforts, which is in excellent agreement with NO2 columns from OMI. The method of objective synoptic weather pattern classification (T-Mode principal component analysis (PCT)) is adopted to distinguish the associated meteorological parameters under various synoptic patterns which governs the variability in regional O3 levels. Among identified synoptic patterns, Type 2 and Type 8 featured by low sea level pressure (SLP), high temperature and strong ultraviolet radiation are most prevalent synoptic patterns in spring and summer, respectively, which are prone to the occurrence of O3 exceedances. This work provides a detailed view of long-term O3 levels and relationship between precursors and meteorological conditions in a typical densely populated city in northern China, showing implications in developing O3 mitigation strategies.